The Influence of Leadership Style, Work Motivation and Organizational Commitment on Employee Performance of DPMD Malang Regency - Wulandari, Juwita; Wilujeng, Sri; Anjar, Arien (IJBLE Scientific Publications Community Inc., 2024)
This study aims to analyse the impact of leadership, work motivation, and commitment among employees of the Malang Regency Community and Village Empowerment Office (DPMD). The validation study is a quantitative study. Data were collected from a questionnaire administered to 52 respondents who were employees of DPMD Malang Regency using the entire sample. Data analysis techniques use multiple linear regression to show the impact of independent variables on the variables. The results showed that: (1) leadership style, work motivation, and organizational commitment have an impact on employee performance; (3) Job support has also been shown to have a positive effect on employee performance. In addition, (4) organizational commitment has also been shown to have a positive effect on employee performance. Wide. The importance of this study shows the importance of using good leadership styles, developing job support and strengthening the commitment of organizations to mobilize staff well